RESPON PENAMBAHAN MINERAL KALSIUM, PHOSPOR, MAGNESIUM DAN SULFUR TERHADAP KARAKTERISTIK CAIRAN RUMEN PADA TERNAK KAMBING LOKAL - Triani Adelina (Jurnal Peternakan, 2005)
Microbial growth and various fertnentation processe5in th~ rumen require an adequate supply of minerals. An experiment was conducted to determine rumen fluid characteristics from 20 goats of local breed. ~ f They were randomly allocated into 4 treatments in a Randomized Block Design with 5 replication. Treatments were: A =forages (natural grasses, gIiricidia and leucaena) and concentrate (rice brand, com graL,,\ and coconut meal) ; B =ration A+Ca+P ; C =ration A+Ca+P+Mg and D = ration A+Ca+P+S. Ration between forages and concentrates is 60 : 40 with TDN 53.94% and CP 13.87%. The result showed that there were no effect of mineral! 1 Ca, P, Mg and S supplementation on the characteristics of the rumen fluid except for VFA even though it was still on the optimum condition for microbial growth. In conclusion, supplementation of Ca, P, and S was the best I among the treatments.